(untitled) (Journal of Social Sciences Review, 2025)
This study examines the impact of Green Human Resource Management (GHRM), Leadership Style on Sustainable Innovation in Pakistan, while mediation is involved of Knowledge Sharing. Quantitative research was applied employing data from 350 employees and managers in sustainability organizations in Pakistan through SEM (Structural Equation Modeling). Results suggest that Green HRM and Leadership Style elevate the effect of Knowledge Sharing on Sustainable Innovation. It is concluded that organizations in Pakistan that implement green HR policies and transformational leadership promote a culture of knowledge sharing in the organization which drives innovation. This thesis makes a contribution to the Resource Based View (RBV) and the Knowledge Based View (KBV) by stressing the importance of human and intellectual capital in sustainability driven innovation. In practical terms, eco-friendly integration of HRM, leadership development and intercorporate knowledge sharing mechanisms are to be undertaken by businesses in Pakistan in order to have maximum sustainability outcomes. This is valuable study, but its cross-sectional design does not allow us to observe the long-term effects, hence it suggests the requirement to complete long term longitudinal studies and be industry specific in Pakistani context. In general, the findings highlight that Green HRM along with the leadership and knowledge sharing strategies can be used effectively to drive sustainable innovation in Pakistan and thus provide the organization a competitive edge in the era of sustainability.